Uma universidade federal pública e popular é possível?: um estudo da UFFS a partir do Campus Laranjeiras do Sul - Przybysz, Wilian (2015)
This dissertation has the general objective of understanding how the Federal University of Southern Border (UFFS), Laranjeiras do Sul Campus, is effective as Public and Popular, oriented to the appreciation of popular knowledge, the regional development and the current production matrix overcoming, without ceasing to be a Higher Education Federal Institution subordinated legal and bureaucratically to the excluding, elitist and reproductive principles of the established social order. In the first part of this work, which involves the chapters 1 and 2, in order to show UFFS as an object of research and Laranjeiras do Sul Campus as its locus, a bibliographical and legal review was performed. Such review presented as central categories universities as social institutions; UFFS and its distinctive history and its unique proposal; the public and the public sphere, with support, especially, from the lessons of Hannah Arendt and Jürgen Habermas; In addition to resorting, mainly, to Paulo Freire, Carlos Brandão and Conceição Paludo to deal with the popular and popular education. In the second part, chapter 3, beyond the description of the methodological pathways, it encompasses the field research itself, with the exposure and analysis of qualitative data produced in the interviews conducted with the Campus Management, the Administrative and Academic Coordination and Coordination of each of the Campus Undergraduate Courses from UFFS Laranjeiras do Sul campus about the ideas that these subjects have about the institutional proposal and the meaning such conceptions have in their daily actions. The third and final part of this work highlighted the contradictory movements of institutional proposal and the possibilities of this new university that does present a way, especially by the proximity with the social movements of the working class.